ROAD SAFETY AWARENESS AMONG UNIVERSITY STUDENTS: CASE STUDY AT MALAYSIA UNIVERSITI TUN HUSSEIN ONN MALAYSIA, JOHOR - Abd Rahman, R.; Mazle, H. A.; Lim, W. M.; Mohd Masirin, M. I.; Hassan, M. F. (Journal of Civil Engineering, Science and Technology, 2021)
This descriptive study aims to assess the knowledge and awareness of road safety among university students. The study was conducted among students in Universiti Tun Hussein Onn Malaysia by means of questionnaire disseminated online via social media with shareable link to a Google form. The respondents were self-selected to participate in this study where their responses were self-administrated. Questionnaire consisted of 3 sections included demographic information, knowledge on road signs and road safety law, and road safety awareness. 371 students participated in this study, 66% of them age 23 to 27 years old, 61% were female, 92.5% of respondents have at least one type of license with majority agreed that occurrence of accidents resulted in an increase in road safety awareness. The study found that more than half of the participants could not recognise road sign like parking totally prohibited and speed limit ends here. While, 38% of them correctly identified posted speed limit for expressway. Overall, participants have fair understanding on road safety. Therefore, road safety programmes and education are still relevant to university students as young drivers on the road which is important to increase safety awareness.